Human enhancement and functional diversity: Ethical concerns of emerging technologies and transhumanism - Miquel-Àngel Serra (Mètode Science Studies Journal: Annual Review)
The concepts of posthuman, transhuman, transhumanism and human enhancement, and their use of emerging technologies, are described together with their scientific and social implications. Genome editing techniques for enhancement purposes, as well as their scientific, societal, and ethical drawbacks are specifically discussed. In particular, we focus on a perspective of personal and collective responsibility and social inclusion, considering all people, with their functional diversity or different abilities. Pros and cons of proposals for radical transformation as endorsed by transhumanism (genome editing), their impact on future generations and on subjects with functional diversity, and the need of a global ethical frame, are discussed.